Conversa a três. SOUZA, Eneida Maria de (org). Correspondência Mário de Andrade & Henriqueta Lisboa. São Paulo: Editora Peirópolis. EDUSP, 2010. - Paiva, Kelen Benfenatti (Aletria: Revista de Estudos de Literatura, 2010)
.